1988
DOI: 10.2118/13866-pa
|View full text |Cite
|
Sign up to set email alerts
|

Considerations for Optimum Fracture Geometry Design

Abstract: This paper gives production forecasts for (1) various equal-proppant-volume fracture geometries with various formation permeabilities, (2) equal fracture lengths with different proppant volumes, and (3) equal fracture lengths and proppant volumes with various proppant distributions. It shows conditions when Prats' relationship for maximum productivity is true and when higher values of dimensionless fracture conductivity are beneficial. These should give the design engineer useful tools when optimizing fracture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1989
1989
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…As an example of the well with most significant deviation in halflength from initial design, the data of the well 59XX of the formation AS-11 from Priobskoe oilfield is presented in Figure 1 combining information from logs, thermometry, DCHSA investigation and fracture redesign. This additional length provides an improved steady state productivity as the dimensionless conductivity Cfd is still larger than 2 [15,16] despite the reduction of propped width but at the expense of a quicker water breakthrough from injection wells. Table 1 shows the final geometry results on this well comparing Integrated Analysis and the initial design from provided by the contractor.…”
Section: Fracture Geometry Investigationsmentioning
confidence: 99%
“…As an example of the well with most significant deviation in halflength from initial design, the data of the well 59XX of the formation AS-11 from Priobskoe oilfield is presented in Figure 1 combining information from logs, thermometry, DCHSA investigation and fracture redesign. This additional length provides an improved steady state productivity as the dimensionless conductivity Cfd is still larger than 2 [15,16] despite the reduction of propped width but at the expense of a quicker water breakthrough from injection wells. Table 1 shows the final geometry results on this well comparing Integrated Analysis and the initial design from provided by the contractor.…”
Section: Fracture Geometry Investigationsmentioning
confidence: 99%
“…However, other studies have confirmed that the optimized hydrocarbon production is often analyzed as the outcome of a balance between the deliverability from the reservoir to the fracture, which is related the effective fracture half length, and the deliverability from the fracture to the wellbore, which is typically associated with fracture conductivity (Bennett et al 1983, Britt and Bennett 1985, Elbel 1988, and Economides and Nolte 2000. As a result, the fracture conductivity is the product of the propped fracture width and the permeability of the propping agent.…”
Section: Introductionmentioning
confidence: 99%
“…Since hydraulic fracturing began in the mid 1980's, production there has doubled or tnpled, jusaying a $75 million investment in the process in 1991 [Chevron World,199 11. Because the method is so expensive, it is used judiciously. Treatments of individual wells, and of whole reservoirs are carefully planned, simulated and monitored [Veatch, 1983a;Veatch, 1983b;Cleary, 1988;Anderson and Phillips, 1988;Economides, 1987;Elbel, 1988;Acharya, 19881. Reservoir engineers need information on the geometry and size of fractures to plan successive stages of fracturing operations in individual wells, and to plan the spacing of fractured wells in a field.…”
Section: Introductionmentioning
confidence: 99%